Alternation between dietary protein depletion and normal feeding cause liver damage in mouse - Caballero, Veronica Jorgelina (2011)
The effect of frequent protein malnutrition on liver function has not been intensively examined. Thus, the effects of alternating 5 days of a protein and amino acid-free diet followed by 5 days of a complete diet repeated three times (3 PFD-CD) on female mouse liver were examined. The expression of carbonic anhydrase III (CAIII), fatty acid synthase (FAS), glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and glutathione S-transferase P1 (GSTP1) in liver were assessed by proteomics, reverse transcriptase-polymerase chain reaction and Northern blotting. The activities of liver GSTs, glutathione reductase (GR) and catalase (CAT), as well as serum glutamic-oxaloacetic transaminase (SGOT) and glutamic-pyruvic transaminase (SGPT) were also tested. Additionally, oxidative damage was examined by measuring of protein carbonylation and lipid peroxidation. Liver histology was examined by light and electron microscopy. Compared with control mice, 3 PFD-CD increased the content of FAS protein (+90%) and FAS mRNA (+30%), while the levels of CAIII and CAIII mRNAs were decreased (-48% and -64%, respectively). In addition, 3 PFD-CD did not significantly change the content of GSTP1 but produced an increase in its mRNA level (+20%), while it decreased the activities of both CAT (-66%) and GSTs (-26%). After 3 PFD-CD, liver protein carbonylation and lipid peroxidation were increased by +55% and +95%, respectively. In serum, 3 PFD-CD increased the activities of both SGOT (+30%) and SGPT (+61%). In addition, 3 PFD-CD showed a histological pattern characteristic of hepatic damage. All together, these data suggest that frequent dietary amino acid deprivation causes hepatic metabolic and ultrastructural changes in a fashion similar to precancerous or cancerous conditions.